“After-effects” in ¹¹¹In(®¹¹¹Cd)-doped Al₂O₃ semiconductor: a modelization from first principles - Darriba, Germán Nicolás (2016)
The phenomena called “electron-capture after-effects” (ECAE) in the pioneering works from La Plata group in the eighties is produced by the electronic relaxation process that occur in the probe-atom ¹¹¹Cd subsequent to the electron-capture (EC) nuclear decay of its father nuclide ¹¹¹In. The ECAE is reflected in time-differential perturbed γ-γ angular correlations (TDPAC) experiments by the presence of time-dependent hyperfine (dynamic) interactions, reversible with the measuring temperature. We propose here that the electronic relaxation of ¹¹¹Cd generates different electronic configurations at the probe-atom, and therefore different electric-field gradients (EFG), which originates the observed dynamic hyperfine interaction. These electronic configurations may survive during the time window of the TDPAC measurement (τ 1/2=84.1 ns, in this case), from a highly ionized initial atomic charge state (generated after the EC nuclear decay) to a final stable state that is not necessarily the ground neutral state, and which depends on the temperature and nature of the host system